Validitas LKPD Berorientasi Metakognitif untuk Mencapai Kompetensi Peserta Didik dalam Pembelajaran Fisika SMA/MA - Rahma Yeni; Amali Putra; Yenni Darvina (PILLAR OF PHYSICS EDUCATION, 2018)
This research is motivated by the demands of Curriculum 2013 on the four dimensions of knowledge taught in physics learning. At the Curriculum 2013 known metacognitive knowledge includes factual knowledge, conceptual knowledge and procedural knowledge. Metacognitive is the ability of students to control cognitive aspects. From the results of previous research, metacognitive knowledge of students is the lowest than the other three knowledges. Based on observation and interview in the school, the achievement of competence of students is still low, one of the causes is not much effort by teachers to develop metacognitive of students. Efforts to develop metacognitive of students can be done with metacognitive strategies. Learning that involves metacognitive is important to improve thinking ability and ability to solve the problems of students. One solution is to develop LKPD (worksheet student) oriented metacognitive strategy. The purpose of this research is to produce LKPD which is can to be used in physic learning, so that it is hoped that the competence of student can be achieved.Research conducted is research and development (R&D) using ADDIE development model that is reduced to the analysis, design and development. The research subjects consisted of three experts as a validator, physics lecturer FMIPA UNP, and two physics teachers to test the practicality of LKPD and one class X MIPA 4 SMA Adabiah Padang as practitioners to give response to LKPD.The result of research shows that LKPD oriented metacognitive strategy is in very valid category by experts with validity value 85,1%, and very practical according to teacher with practicality value 85,4% and is in practical category according to students with value 79,9%.